ANALYSIS OF KNOWLEDGE MANAGEMENT, TALENT MANAGEMENT, EMPLOYEE RECOGNITION ON EMPLOYEE PERFORMANCE MEDIATED BY EMPLOYEE ENGAGEMENT - Alden Nelson; Hendri Gunawan (SEAN Institute, 2023)
This study aims to determine the analysis of knowledge management, talent management, employee recognition, on employee performance which is mediated by employee engagement. The respondents in this study were the employees who worked in a manufacturing company located in Batam. The sampling technique used was purposive sampling technique with 190 respondents. Smart PLS 3.0 is used to process questionnaire data in data analysis. The results of this study indicate that knowledge management, talent management have a significant effect on employee engagement and employee performance, while employee recognition has no significant effect on employee performance.